Marine radiocarbon reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic Coast of North America - Rick, Torben C.; Henkes, Gregory A.; Lowery, Darrin L.; Colman, Steven M.; Culleton, Brendan J. (Quaternary Research, 2012)
Radiocarbon dates from known age, pre-bomb eastern oyster (Crassostrea virginica) shells provide local marine reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic coastal area of eastern North America. These data suggest subregional variability in ∆R, ranging from 148 ± 46 14C yr on the Potomac River to − 109 ± 38 14C yr at Swan Point, Maryland. The ∆R weighted mean for the Chesapeake's Western Shore (129 ± 22 14C yr) is substantially higher than the Eastern Shore (− 88 ± 23 14C yr), with outer Atlantic Coast samples falling between these values (106 ± 46 and 2 ± 46 14C yr). These differences may result from a combination of factors, including 14C-depleted freshwater that enters the bay from some if its drainages, 14C-depleted seawater that enters the bay at its mouth, and/or biological carbon recycling. We advocate using different subregional ∆R corrections when calibrating 14C dates on aquatic specimens from the Chesapeake Bay and coastal Middle Atlantic region of North America.
id: 2155